What Drives Emerging Stock Market Returns? A Factor-Augmented VAR Approach. Issue 5 (9th April 2022) - Kwon, Dohyoung
ABSTRACT: This paper explores the dynamic relationship between global economic factors and emerging stock returns within a factor-augmented VAR model. I find that favorable global growth and stock market shocks have significant positive effects on emerging equity returns, whereas global uncertainty and US dollar exchange rate shocks cause a substantial fall in the returns. Global oil shocks lead to a transient increase in emerging stock returns, followed by a gradual decline. Variance decomposition analysis implies that the global uncertainty shock is the most important in the short run, explaining more than 30% of the fluctuation in emerging stock returns, while the US dollar exchange rate shock becomes the most critical in the long run, explaining more than 40%. These findings have crucial implications for international investors, as well as for policymakers in emerging market economies.